Yizani Sifunde: How a multi-pronged intervention strengthened teaching and learning in ECD centres - von Blottnitz, Magali (Liberty Community Trust, Wordworks, Book Dash and Nal'ibali, 2024)
This is the fourth in a series of learning briefs that explore the design, implementation and impact of Yizani Sifunde, a collaborative multi-pronged intervention designed to boost early literacy outcomes in 4- and 5-year-olds. This brief focuses on: • the changes the project made possible in early childhood development (ECD) centres, related to resources, practitioner attitudes and teaching practices, centre management, and overall ECD quality; • how durable these shifts were; and • how these shifts contributed to young children’s development. It finds that, for the participating ECD centres, the Yizani Sifunde intervention led to radically improved access to learning materials, better equipped book corners, improved confidence of practitioners with story-based literacy activities. The brief also reveals improvements in the ECD practitioners' experience of parental engagement. Areas where there was still room for improvement include emerging writing and the children's independent use of book corners remain. The brief further provides multiple sources of data revealing that the practices of the intervention have been largely sustained after project exit.
Exploring the impact of a collaborative, multi-pronged early literacy intervention on 4- and 5-year-olds - Brief 4
Yizani Sifunde (isiXhosa for “come, let’s read”) aimed to boost early literacy outcomes at under-resourced early childhood development (ECD) centres in the Eastern Cape. It was implemented in three one-year cycles between 2021 and 2023. The project was initiated and funded by the Liberty Community Trust, and jointly designed and delivered by three literacy nonprofits: Book Dash, Nal’ibali and Wordworks. Local Eastern Cape partners ITEC and Khululeka supported implementation. Social Impact Insights Africa carried out the external evaluation. More information on the Yizani Sifunde project can be found on https://bookdash.org/yizani-sifunde/ This Learning Brief was written for the Yizani Sifunde project by Dr Magali von Blottnitz, with input from other project partners. It draws extensively on an external evaluation conducted by Social Impact Insights Africa. Liberty Community Trust holds the intellectual property rights to the evaluation results and gave permission for them to be shared subject to specific acknowledgements.
Keywords: Early learning; Early literacy; Early Childhood Development; Yizani Sifunde; South Africa; Eastern Cape; ECD centres; Liberty Community Trust; Wordworks; Nal'ibali; Book Dash; Khululeka; ITEC; Impact Evaluation; ECERS; Learning Programme Quality Assessment; LPQA; Triple-Cocktail approach; Children's Books; Book ownership; Little Stars; Story Sparkers; Reading; Social Impact Insights Africa; ECD classroom; Pre-Grade R; Practitioner training; Book corners; storytelling; child engagement